PENGARUH PEMBERIAN COKELAT HITAM TERHADAP INTENSITAS NYERI DISMENORE PRIMER PADA REMAJA PUTRI - Nurfaizah Alza; Nanda Wahyudi; Veny Delvia Pombaile; Nurhidayah (JOMIS (Journal of Midwifery Science), 2026)
Dysmenorrhea is a common symptom affecting approximately 60% of women during menstruation. Among teenegers, the main cause of dysmenorrhea is primary dysmenorrhea. Primary dysmenorrhea can influence quality of life, daily activities, learning ability and class attendance, even career achievements. The research results indicate that 13.1% of teenagers were absent from school, which corresponds to a 73% prevalence of dysmenorrhea; among the 52 students (81.3%) who experienced dysmenorrhea, 36 students (56.3%) reported having a low quality of life. One of the attempts that can be done to minimize dysmenorrhea pain is by consuming dark chocolate. Dark chocolate contains more beneficial compounds, such as flavanols The purpose of this study is to know the effect of dark chocolate consumption on the intensity of primary dysmenorrhea pain in teenage girls. The method used is a quasi-experiment with a one-group pretest-posttest design. The respondents in this study are the 10th-grade female students of SMA Negeri 2 Gorontalo. The sampling technique used is purposive sampling, with a sample size of 34 individuals determined based on the inclusion and exclusion criteria set. The inclusion criteria for this study are that the participants are 11th-grade female students of SMA Negeri 2 Gorontalo. The participants must be willing to be respondents and sign the informed consent form, menstruate monthly, experience primary dysmenorrhea, be aged 15-17 years, and enjoy dark chocolate. The exclusion criteria are secondary dysmenorrhea, chocolate allergy, undergoing special treatment, suffering from certain diseases, and not being in the menstrual cycle. The data were analyzed using a paired sample t-test. The results obtained show a decrease in the average intensity of primary dysmenorrhea pain before and after the consumption of chocolate by 1.96, with a p-value of 0.000 (p < 0.05), indicating that statistically, there is an effect of dark chocolate consumption on the intensity of primary dysmenorrhea pain in teenage girls. Recommendation for adolescents to consume dark chocolate during dysmenorrhea and for healthcare providers will consider making dark chocolate as part of the material in providing care to teenagers and the general public, especially in managing dysmenorrhea